Holocene paleogeographic evolution of an ancient port city of the central Mediterranean area: Natural and anthropogenic modifications from Salerno city, southern Italy. Issue 3 (27th November 2019) - Amato, Vincenzo; Aiello, Giuseppe; Barra, Diana; Caporaso, Lucia; Caruso, Tonino; Giaccio, Biagio; Parisi, Roberta; Rossi, Amedeo
Abstract: A multidiplisciplinary study, including geomorphological, lithostratigraphical, geochronological, geochemical, and paleontological investigations, was carried out in the coastal area of Salerno city, southern Italy. The study aimed to outline the Late Glacial‐Holocene geoenvironmental evolution of Salerno's port area in response to both natural and anthropogenic factors. The geomorphological study included an examination of historic maps, which enabled a detailed reconstruction of the coastal landscape change during historic times. Lithostratigraphical analyses of three new boreholes, supported by radiocarbon and tephrochronological data, and of previously retrieved core‐successions and archaeological trenches, extends our reconstruction of the paleogeographical evolution of the Salerno coastal area back to the Late Pleistocene. Geochemical and paleontological analyses of samples from the newly acquired cores were combined with the lithofacies analyses of previously retrieved cores to detect ancient harbors in the area of the current port facilities of the city and surrounding urban areas. This work contributes to scientific debate about the specific sedimentary architectures and geochemical properties of the Salerno harbor environment and refines methodological approaches for characterizing and assessing the evolution and demise of ancient port facilities in Mediterranean coastal cities.